Atomic-scale tailoring of spin susceptibility via non-magnetic spin-orbit impurities. Issue 1 (December 2018) - Womack, F.; Adams, P.; Nam, H.; Shih, C.; Catelani, G.
Abstract Following the discovery of topological insulators, there has been a renewed interest in superconducting systems that have strong spin-orbit (SO) coupling. Here we address the fundamental question of how the spin properties of a otherwise spin-singlet superconducting ground state evolve with increasing SO impurity density. We have mapped out the Zeeman critical field phase diagram of superconducting Al films that were deposited over random Pb cluster arrays of varying density. These phase diagrams give a direct measure of the Fermi liquid spin renormalization, as well as the spin orbit scattering rate. We find that the spin renormalization is a linear function of the average Pb cluster -to- cluster separation and that this dependency can be used to tune the spin susceptibility of the Al over a surprisingly wide range from 0.8χ0 to 4.0χ0, whereχ 0 is the non-interacting Pauli susceptibility. The effect of spin orbit interactions on a typical BCS superconductor is becoming an important area of research for phenomena such as Majorana fermions and topological superconductivity. The authors investigate the effect of Pb clusters on the spin susceptibility of superconducting Al films via spin orbit interactions.